Cyclosporin A reverses vincristine and daunorubicin resistance in acute lymphatic leukemia in vitro. - Slater, L M (1986)
The development of drug resistance by tumor cells is a major obstacle to the cure of human malignancy. Cyclosporin A (CsA) completely reverses primary resistance to vincristine and cross resistance to daunorubicin in a pleiotropic drug-resistant subline of human T cell acute lymphatic leukemia. This subline is over 50-fold resistant to vincristine and fivefold resistant to daunorubicin. CsA has little effect on vincristine or daunorubicin activity in drug-sensitive parental leukemia and corrects daunorubicin resistance without altering cellular daunorubicin accumulation.